A BIBLIOGRAPHICAL STUDY ON PEACE OF GANDHI'S YOUNG INDIA :GANDHI A PEACE COMMUNICATOR - Dr. K. Victoriamma (Galaxy International Interdisciplinary Research Journal, 2023)
Now-a-days all the news papers contains ,conflict events covers a prominent role in news paper and in journalism.The conflicts is in between individuals ,communities ,states , nations and international .The news paperss are advertently intencify the conflicts by giving it in a different angel in the story . The Language used in such reports are sharp motivates further gaps in the group involves the groups . At this junction media has to play a vital to resolve the conflict and strive for resolution. Thus the peace journalism bridge the gap between the parties involved and strive for amicable solution of peace (McGoldrick, and Lynch, 2000).Gandhi taken lead to bridge the gap between the parties ,emphasised on conflict reduction, promotion of peace journalism .Gandhi advocated peace through the publication of peace articles in his journals i,e Young India. He havebeen writing on peace aritles in YoungIndia,one total issuse is dedicated to Non-violance in Young India on August 11, 1920, with the title ‘The doctrine of the sword’ The present study confined to coverage pattern on 'peace' theme in Young India used content anylysis as a method to observe the 'frequency', 'distribution','place',and 'space'.